Program Semanggi Berbasis Kāfalah pada Lembaga Manajemen Infaq Surabaya dalam Perspektif Hukum Islam - Siti Masruroh (Islamic Economic Law Programs, Faculty of Sharia and Law State Islamic University (UIN) of Sunan Ampel Surabaya., 2020)
.This research focuses on the kafālah-based Semanggi Program at the Infaq Management Institute in Surabaya. This research analyzes the concept of kafālah from the perspective of Islamic law. The research method applies qualitative methods to collect data employing observation, interviews, and documentaries. The next stage is to apply the descriptive analysis method to understand the concept of the kafālah-based Semanggi program. The construction of understanding uses deductive logic. The results of the research construction on the Semanggi Program have not fully implemented the characteristics of kafālah according to Islamic law. Based on field data, there is no kafālah contract between Mākful Lahu (people who owe debts) and Mākful 'Anhu (people who are guaranteed), namely the teachers of the al-Qur'an Education Park to make a debt-receivable agreement. In the perspective of Islamic law, it is not included in the category of the kafālah contract because the characteristics of the concept of kafālah are incomplete. This research concludes that the Surabaya Infaq Management Institute must reconstruct the concept of kafālah so as not to harm other parties and the Surabaya Infaq Management Institute. Giving gifts based on Islamic law can be an alternative to the kafālah contract.